2021
DOI: 10.3390/w13192666
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Leaf Water Status and Grain Yield of Wheat under Different Irrigation Regimes Using Optimized Two- and Three-Band Hyperspectral Indices and Multivariate Regression Models

Abstract: Spectral reflectance indices (SRIs) often show inconsistency in estimating plant traits across different growth conditions; thus, it is still necessary to develop further optimized SRIs to guarantee the performance of SRIs as a simple and rapid approach to accurately estimate plant traits. The primary goal of this study was to develop optimized two- and three-band vegetation- and water-SRIs and to apply different multivariate regression models based on these SRIs for accurately estimating the relative water co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 88 publications
1
11
0
Order By: Relevance
“…The same type of SRIs exhibits high multicollinearity among themselves, which reduces the ability of such indices to detect a variation among genotypes that exhibit similar reflectance and absorption behavior. Therefore, previous studies have reported that using a combination of SRIs and multivariate regression models such as PLSR can overcome these limitations and significantly improve the predication accuracy of relevant plant traits [43,52,54,80,82,[84][85][86][87][88][89]. Most of these studies reported that using several SRIs in tandem with the PLSR model resulted in better performance in the estimation of plant traits, such as plant biomass, grain yield, and plant water content, as compared with a single index.…”
Section: Prediction Of Plant Biomass and Biological Yield Based On Plsrmentioning
confidence: 99%
“…The same type of SRIs exhibits high multicollinearity among themselves, which reduces the ability of such indices to detect a variation among genotypes that exhibit similar reflectance and absorption behavior. Therefore, previous studies have reported that using a combination of SRIs and multivariate regression models such as PLSR can overcome these limitations and significantly improve the predication accuracy of relevant plant traits [43,52,54,80,82,[84][85][86][87][88][89]. Most of these studies reported that using several SRIs in tandem with the PLSR model resulted in better performance in the estimation of plant traits, such as plant biomass, grain yield, and plant water content, as compared with a single index.…”
Section: Prediction Of Plant Biomass and Biological Yield Based On Plsrmentioning
confidence: 99%
“…The main advantage of the RF model is the flexibility to variable distribution and it is not at risk to abnormal outputs and/or noise, and also an advanced-dimensional data-sensitive model. The RF model is a reliable model against over-fitting and it has been utilized efficiently in solving regression problems [49]. These two methods involve a great number of spectral or band-ratio indices into a single index to elevate the detection of measured crop characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…The RSI was determined by combining two separate wavelengths in the 302-1148 nm (Figure 1). According to Elsayed et al [34], the contour maps of spectral reflectance of spectrum region were created. The established maps are useful for determining the ideal spectral region with effective (optimized) wavelengths and recognizing the relevance of SRIs.…”
Section: Selection Of Sris Of Banana Fruitsmentioning
confidence: 99%